2001
DOI: 10.1146/annurev.ecolsys.32.081501.114034
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the Study of Territory Size and Shape

Abstract: ▪ Abstract  Intraspecific variation in territory size and shape can have strong effects on population structure and dynamics. The traditional theoretical approach to the study of territory size is based on optimality models that analyze decisions of focal residents as responses to the costs and benefits of defense. These models have stimulated numerous empirical studies showing that territory holders adjust their behavior according to rates of intrusion and availability of food. However, models of optimal terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
300
3
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(352 citation statements)
references
References 153 publications
20
300
3
11
Order By: Relevance
“…Recent studies (3,4) advocate the need to develop a general framework to explain the broad spectrum of spacing behavior we observe: from one extreme condition, with full territorial exclusion, to an intermediate situation, with overlapping home ranges, to the other extreme, with free-ranging animals that fully share the available space. Animals that deposit marks over the terrain represent a model animal system to develop such a framework.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (3,4) advocate the need to develop a general framework to explain the broad spectrum of spacing behavior we observe: from one extreme condition, with full territorial exclusion, to an intermediate situation, with overlapping home ranges, to the other extreme, with free-ranging animals that fully share the available space. Animals that deposit marks over the terrain represent a model animal system to develop such a framework.…”
mentioning
confidence: 99%
“…Here, we move beyond that limitation by analyzing the collective emergence of spacing patterns resulting from animals' avoidance. We chose to focus on the endogenous mechanisms of how patterns are generated rather than asking why animals do it, which depends on the resources they aim to defend (3).…”
mentioning
confidence: 99%
“…Adams (2001) reviewed experimental and theoretical works on home range and territory size, and showed that interactions among neighbouring individuals or groups directly shape their territory boundaries. Two main hypotheses have been proposed to explain the outcome of intergroup competition: the Group Augmentation hypothesis (GA: Kokko et al 2001;Bergmüller et al 2007) and the realized Resource Holding Potential (rRHP) hypothesis (Crofoot et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Because patch shape, along with area, determines the amount of habitat exposed to edges, patch shape may have a signifi cant eff ect on habitat occupancy by birds. Among birds, which are oft en strongly territorial, perch availability (Yosef, Grubb, 1994) and food and nesting sites appear to be particularly relevant to territory confi guration (Adams, 2001;Rolando, 2002).…”
Section: Discussionmentioning
confidence: 99%